2019
DOI: 10.17159/2078-5151/2019/v57n3a2928
|View full text |Cite
|
Sign up to set email alerts
|

The profile of thyroid cancer in patients undergoing thyroidectomy at Chris Hani Baragwanath Academic Hospital

Abstract: Background: The histological type of thyroid cancer in well-resourced countries is predominantly papillary. Follicular carcinoma is predisposed by iodine deficiency that was present the Black population of South Africa until salt iodination in 1995. The aim of this study was to analyse the profile of thyroid cancer in Black South Africans from January 2001 to December 2017 and to identify any temporal changes in thyroid cancer histological subtypes since salt iodination. Method: Histopathological reports of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…This predominance of follicular carcinoma reported in this study is similar to previous studies from Sudan[ 20 , 21 ] and prior studies on TC conducted in Southern Africa [ 36 – 38 ], Western Africa [ 39 , 40 ], and Eastern Africa [ 38 , 41 ]. However, there are studies conducted in Africa which showed papillary carcinoma as the most frequent type of TC [ 33 , 42 45 ]. In the African continent, there is a wide variation in the prevalence rates of histological types of TC as follows: papillary (6.7–72.1%), follicular (4.9–68%), anaplastic (5–21.4%) and medullary (2.6–13.8%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This predominance of follicular carcinoma reported in this study is similar to previous studies from Sudan[ 20 , 21 ] and prior studies on TC conducted in Southern Africa [ 36 – 38 ], Western Africa [ 39 , 40 ], and Eastern Africa [ 38 , 41 ]. However, there are studies conducted in Africa which showed papillary carcinoma as the most frequent type of TC [ 33 , 42 45 ]. In the African continent, there is a wide variation in the prevalence rates of histological types of TC as follows: papillary (6.7–72.1%), follicular (4.9–68%), anaplastic (5–21.4%) and medullary (2.6–13.8%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 illustrates the rising trend in the incidence of thyroid cancer in some selected countries across the world although the rate of rise differs due to genetic variations, environmental factors and access to medical care. [5][6][7] The rate of rise of thyroid cancer incidence in Africa is lower than most parts of the world probably due to underdiagnosis. 4 Thyroid cancer is commoner in females and it is the 5th most common cancer among females accounting for 4.9% of cancer incidence in them.…”
Section: Introductionmentioning
confidence: 99%
“…
Thyroid cancer is prevalent both internationally and locally in South Africa (SA), [1] and is the most common cause of endocrine malignancy in Africa. [1] Rahbari et al [2] found that it is 2.9 times more common in females than males, and is currently on an increasing trend worldwide.
…”
mentioning
confidence: 99%
“…
Thyroid cancer is prevalent both internationally and locally in South Africa (SA), [1] and is the most common cause of endocrine malignancy in Africa. [1] Rahbari et al [2] found that it is 2.9 times more common in females than males, and is currently on an increasing trend worldwide. [1] This increase may be due to various factors, including improvements in diagnostic methods and changes in iodination of salt in our diets.
…”
mentioning
confidence: 99%
See 1 more Smart Citation